Analisis Yuridis Pekerjaan Tambah Kurang dalam Proyek Pembangunan Fasilitas Penunjang pada Pasar Bukit Duri Menurut Peraturan Presiden No 54 Tahun 2010 tentang Pengadaan Barang dan Jasa - Yeny Setiarini; Adi Sujatno; Umar Aris (Syntax Literate, 2023)
Indonesia is currently experiencing a demographic bonus. Based on population census data in 2020, 70.72% of Indonesia's population is of productive age, this shows that the current level of consumption and transactions is increasing. Indonesian people tend to make transactions to meet their daily needs in traditional markets or modern markets. However, currently there are not many traditional market facilities and they are not feasible. Based on data from Perumda Pasar Jaya to date, 40% of traditional markets in the Jakarta area are unfit for habitation and must be totally revitalized. One of them is the thorn hill market. PT TDPM successfully won the project tender to support the Bukit Thorn market facility organized by the market manager. However, at this stage of the work process, some more or less work occurs. In this study, researchers examined whether there was a lack of work that occurred in the Bukit Durian market facility supporting project after it was in accordance with Presidential Regulation Number 54 of 2010? And what is the fact that there is less and less work being carried out in PT TDPM's Bukit Duri market project?. This study uses data collection techniques of observation, documentation and interviews. Based on the research that has been done by researchers, in fact the additional work carried out by PT TDPM is not in accordance with presidential regulation number 54 of 2010 where the weight is almost 16% of the project value. To address this, there is less work to be done and some work items are provided voluntarily by TDPM in the hope of maintaining a relationship with the project manager. Based on this, the researcher provides a recommendation to review the provisions regarding the addition of working weights of less than a maximum of only 10% based on Presidential Decree No. 54 of 2010. If it is not reviewed, it can lead to the potential for corruption, collusion, and nepotism.